2018
DOI: 10.1111/ped.13554
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam as a first‐line treatment for neonatal seizures: Retrospective study

Abstract: Midazolam is commonly used to treat refractory seizures in newborns and as a first-line anti-epileptic drug in children. Its use as first-line treatment of neonatal seizures has not been investigated so far. We retrospectively studied the tolerability of midazolam in 72 newborn infants who received i.v. or i.n. midazolam as first-line treatment for seizures. No major side-effect exclusively due to midazolam was reported. The i.n. route was used for 20 patients (27.8%). Effectiveness could not be formally evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…48 A recent clinical study on midazolam as a first-line treatment for neonatal seizures reported that the drug was well tolerated and suggested that, given its short half-life, it might be considered a useful, easy-to-use agent to stop ongoing seizures or break a cluster of seizures in neonates. 76 The present data indicate that disease-modifying efficacy is an added advantage of midazolam in neonates. That such efficacy may occur in human neonates was indicated by a study in which midazolam was administered after PB failed, which resulted in rapid control of seizures and significantly improved long-term neurodevelopment, which, however, was only assessed at 1 year of age.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…48 A recent clinical study on midazolam as a first-line treatment for neonatal seizures reported that the drug was well tolerated and suggested that, given its short half-life, it might be considered a useful, easy-to-use agent to stop ongoing seizures or break a cluster of seizures in neonates. 76 The present data indicate that disease-modifying efficacy is an added advantage of midazolam in neonates. That such efficacy may occur in human neonates was indicated by a study in which midazolam was administered after PB failed, which resulted in rapid control of seizures and significantly improved long-term neurodevelopment, which, however, was only assessed at 1 year of age.…”
supporting
confidence: 51%
“…Such comparison is needed in human neonates 48 . A recent clinical study on midazolam as a first‐line treatment for neonatal seizures reported that the drug was well tolerated and suggested that, given its short half‐life, it might be considered a useful, easy‐to‐use agent to stop ongoing seizures or break a cluster of seizures in neonates 76 . The present data indicate that disease‐modifying efficacy is an added advantage of midazolam in neonates.…”
Section: Discussionmentioning
confidence: 63%
“…Dao et al studied the use of midazolam (intravenous or intranasal) as first-line therapy for neonatal seizures in 72 neonates. 52 Though effectiveness could not be confirmed due to the absence of EEG monitoring, midazolam was well tolerated in both routes. GABAergic drugs are speculated to be less effective inhibitors during the neonatal age group due to a higher relative expression of chloride transporters NKCC1, which leads to higher intracellular chloride concentration.…”
Section: First-and Second-line Therapy and Relevant Studiesmentioning
confidence: 99%
“…Available data regarding the use of benzodiazepines in neonates for seizures are primarily limited to retrospective studies. The response rate is varied with complete seizure response occurring in < 20% of neonates treated with 0.1 mg/ kg midazolam as first-line treatment [61] and between 0 and 100% when midazolam or clonazepam are used as secondline treatment for ongoing seizures [62][63][64]. Nearly half of the neonates treated with midazolam as first-line treatment had continued seizures [61]; given the limitations in study design this number may, in fact, be higher.…”
Section: Benzodiazepinesmentioning
confidence: 99%